Juridical "Joy": Law, Affect and the Anecdote. (October 2016) - Temple, Kathryn
Legal anecdotes serve to bind populations to law through creating an affective, even affectionate, relationship between law and its communities. An analysis of a legal anecdote involving Justice John Holt (1642–1710) and witchcraft demonstrates how anecdotes can soothe public anxieties over rapid modernization. This particular anecdote asserts the primacy of the literate over the oral, high culture over popular culture, science over superstition, the urban over the rural, and yet creates in the end an affective community united around affection for Holt and the English common law system he represented.